2006
DOI: 10.1038/nature05107
|View full text |Cite
|
Sign up to set email alerts
|

An intron with a constitutive transport element is retained in a Tap messenger RNA

Abstract: Alternative splicing is a key factor contributing to genetic diversity and evolution. Intron retention, one form of alternative splicing, is common in plants but rare in higher eukaryotes, because messenger RNAs with retained introns are subject to cellular restriction at the level of cytoplasmic export and expression. Often, retention of internal introns restricts the export of these mRNAs and makes them the targets for degradation by the cellular nonsense-mediated decay machinery if they contain premature st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
161
0
6

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 126 publications
(173 citation statements)
references
References 27 publications
6
161
0
6
Order By: Relevance
“…When TAP is tethered to pre-mRNA or over expressed it stimulates the direct export of pre-mRNA (23). Simple retroviruses and TAP pre-mRNA have taken advantage of this property by evolving specific high-affinity RNA elements that directly bind TAP, recruiting it and promoting export of RNAs that would normally be exported inefficiently (29,30). Were TAP to directly bind all cellular pre-mRNAs efficiently, it might lead to premature export, a disastrous situation for the cell, so it is likely that this process is regulated.…”
Section: Discussionmentioning
confidence: 99%
“…When TAP is tethered to pre-mRNA or over expressed it stimulates the direct export of pre-mRNA (23). Simple retroviruses and TAP pre-mRNA have taken advantage of this property by evolving specific high-affinity RNA elements that directly bind TAP, recruiting it and promoting export of RNAs that would normally be exported inefficiently (29,30). Were TAP to directly bind all cellular pre-mRNAs efficiently, it might lead to premature export, a disastrous situation for the cell, so it is likely that this process is regulated.…”
Section: Discussionmentioning
confidence: 99%
“…Although there have been extensive studies on the function of NXF1, much less is known about the regulation of its expression. However, the Hammarskjöld group (28) has recently demonstrated that there exists at least one alternatively spliced Nxf1 variant that encodes a truncated form of NXF1 and that the expression of this variant is regulated by the full-length NXF1. Our findings represent yet another mechanism of Nxf1 regulation.…”
Section: Discussionmentioning
confidence: 99%
“…Subcellular fractionation and protein extraction Subcellular fractionation was performed as described by Li et al [19]. Briefly, cells were lysed for 15 min on ice using a Triton X-100 lysis buffer (50 mmol/l Tris/HCl, pH 7.5, 0.5% Triton X-100, 137.5 mmol/l NaCl, 10% glycerol, 1 mmol/l sodium vanadate, 50 mmol/l NaF, 10 mmol/l sodium pyrophosphate, 5 mmol/l EDTA and the Protease Inhibitors Cocktail [Sigma, St Louis, MO, USA]).…”
Section: Methodsmentioning
confidence: 99%